Unraveling the Role of Motivation in English Reading Comprehension - Sadikin, Hamim; Anggia, Helta; Zsuzsa , Kaló; Lakatos, Kristóf (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research investigates the motivational factors influencing English reading comprehension among 101 grade 12 students, utilizing Dörnyei's L2 Motivational Self-System (L2MSS) to analyze the roles of Ideal L2 Self (ILS), Ought-to L2 Self (OLS), and Learning Experience (LE). The study employed a quantitative correlational design. Data were gathered via a motivation survey and the Quick Placement Test (QPT), then analyzed using Structural Equation Modeling (SEM) and the Rasch Model to verify construct validity and test the hypothesized relationships. Findings indicate that ILS has a beneficial effect on LE, yet shows a negative correlation with reading comprehension, implying that idealized self-perceptions might obstruct performance. OLS exert a beneficial effect on both LE and Reading comprehension, underscoring the importance of balancing intrinsic and extrinsic motivation. LE shows a strong correlation with ILS and OLS, yet it does not directly influence reading comprehension, suggesting that other elements might be involved. Results emphasize the complex nature of motivation in reading comprehension and the significance of nurturing educational settings that align students’ objectives with attainable results.